2017
DOI: 10.1186/s12876-017-0662-1
|View full text |Cite
|
Sign up to set email alerts
|

Partially covered metal stents have longer patency than uncovered and fully covered metal stents in the management of distal malignant biliary obstruction: a retrospective study

Abstract: BackgroundSelf-expandable metal stents (SEMSs) are widely used for malignant biliary obstructions. Nitinol-covered SEMSs have been developed to improve stent patency. Currently, SEMSs may be uncovered, partially covered, or fully covered; however, there is no consensus on the best stent type for the management of malignant distal biliary obstruction (MDBO).MethodsPatients with unresectable MDBO receiving SEMS (Wallflex™) were retrospectively analyzed. Time to recurrent biliary obstruction (TRBO) and survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…The rate of stent migration also did not differ significantly (14 vs. 8%; P = 0.113). The results are similar to a recent retrospective analysis by Yokota et al [7] comparing the clinical outcome of uncovered, partially covered, and fully covered of Wall-Flex™ stents in patients with MBO. Although there was no significant difference in patient survival among the three groups, the rate of RBO was numerically, but not statistically significantly lower with partially covered SEMSs (28.6%) as compared to uncovered (45.4%; P = 0.215) and fully covered (55.2%; P = 0.106) stents.…”
supporting
confidence: 89%
“…The rate of stent migration also did not differ significantly (14 vs. 8%; P = 0.113). The results are similar to a recent retrospective analysis by Yokota et al [7] comparing the clinical outcome of uncovered, partially covered, and fully covered of Wall-Flex™ stents in patients with MBO. Although there was no significant difference in patient survival among the three groups, the rate of RBO was numerically, but not statistically significantly lower with partially covered SEMSs (28.6%) as compared to uncovered (45.4%; P = 0.215) and fully covered (55.2%; P = 0.106) stents.…”
supporting
confidence: 89%
“…Recent studies have revealed that fully covered SEMS (FCSEMS) that are used for MDBO treatment have low stent migration rates and trigger few cholecystitis events [51]. A prospective study of unresectable pancreatic cancer with obstructive jaundice demonstrated a significantly longer survival time and no stent dysfunction for covered SEMS with an anti-migration system than it did without an anti-migration system [52,53]. These studies suggest that covered SEMS are a valuable and cost-effective option for MDBO treatment because of their increased patency, less tumor in-growth, and easy removal [53,54].…”
Section: Stent Selectionmentioning
confidence: 99%
“…A prospective study of unresectable pancreatic cancer with obstructive jaundice demonstrated a significantly longer survival time and no stent dysfunction for covered SEMS with an anti-migration system than it did without an anti-migration system [52,53]. These studies suggest that covered SEMS are a valuable and cost-effective option for MDBO treatment because of their increased patency, less tumor in-growth, and easy removal [53,54]. However, several recent large studies [55][56][57] and a recent meta-analysis from Canada [58] have revealed no clear benefit of FCSEMS over uncovered SEMS (UCSEMS) in terms of stent patency and complications.…”
Section: Stent Selectionmentioning
confidence: 99%
“…While SEMSs pushed the service life of the stents to 6 months or longer, they also have drawbacks, for instance getting embedded into the duct walls. Covering the metal wire with polymers solved this issue, but increased the risk of stent migration, albeit the covered SEMSs may offer generally a lower risk of dysfunction [165] in spite of previous different opinions [166].…”
Section: Biliary and Pancreatic Stentsmentioning
confidence: 99%